Pengaruh Rasio Profitabilitas Terhadap Nilai Perusahaan (Studi Kasus pada Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia pada Tahun 2018-2020) - Filzah Gaissani; Ronny Malavia Mardani; Ita Athia (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to find out how the effect of the profitability ratio on the value of the case study company on the food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2018-2020. The population in this study are all food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period with a total of 31 food and beverage sub-sector companies. Sampling technique using purposive sampling method obtained a sample of data as many as 16 companies in the food and beverage sub-sector. This research data collection method uses the method of data documentation listed in the annual report at IDX. The data analysis technique in this study used panel data regression with software eviews 9. The results showed that the net profit margin (NPM) had a negative and insignificant effect on firm value. The results showed that return on assets (ROA) had a negative and insignificant effect on firm value. The results show that return on equity (ROE) has a positive and significant effect on firm value.Keywords : Price to Book Value, Net Profit Margin, Return On Asset, dan Return On Equity.